Floating on Mercury in the Moonlight: “Birkat az-Zi?baq” in the Palace of Khum?rawa?h in al-Qa???i? - Krol, Alexei A..
In the article the author analyzes references to a basin filled with mercury (“Birkat az-Zi?baq”) in the palace of the Tulunid Dynasty ruler Khum?rawa?h in al-Qa???i?. This basin, which has been mentioned in several medieval Arabic sources (al-Maqr?z?, Ibn Duqma?q, Ibn Iy?s, Ish??q?) had been built in order to heal Khum?rawa?h of insomnia. According to al-Maqr?z?, the basin has the dimensions of 50 x 50 cubits (ca. 25 x 25 m), however the depth of the basin has not been mentioned. The author critically analyzes the known references of the mercury basins in the palaces of Muslim rulers and advances several hypotheses explaining the construction of the basin in the palace of Khum?rawa?h.